(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2016)
The present work is devoted to analysis of geological and geophysical models in prospecting chromite ores. Two types of physical and geological prospecting models have been compared: the first, when the chromite ore is manifested in the form of direct anomalies in geophysical fields and second, when the ore bodies occur in conjunction with their enclosing rocks.